P29 Predictive value of p16/Ki-67 dual-stained cytology for the progression of cervical dysplasia. (1st November 2019) - Lee, YK; Hong, SR
Abstract : Introduction/Background: Dual immunocytochemistry for p16/Ki-67 has been reported as a useful biomarker to identify cells of underlying high-grade cervical intraepithelial neoplasia in the Papanicolaou (Pap) cytology. Regression rates for atypical squamous cells of undetermined significance (ASCUS) or low-grade squamous intraepithelial lesion (LSIL) range widely, from 30% to 80%. The objective of this study was to investigate the predictive value of p16/Ki-67 dual-stained cytology for the progression of disease. Methodology: Cytology p16/Ki-67 dual-staining test was performed on 691 liquid-based residual samples from a cohort of women with ASC-US/LSIL and co-testing human papillomavirus (HPV) positive. Among them, 250 women were followed up for at least a year. Study end points were HSIL detection in 1 and 2 year's follow-up. Results: Positivity of p16/Ki-67 dual stained cytology was well correlated to progression of disease compared with positivity of HPV 16/18. During 1 year follow-up, 23 of 250 women experienced progression of disease into HSIL. For positivity of p16/Ki-67 dual stained cytology, Sensitivity (60.9%) for the detection of HSIL or specificity (81.5%) for normal or low grade cytology was higher than those of HPV 16/18 tests (13.0% and 89.0%, respectively) (p<0.001). During 2 years follow-up, 11 of 190 women experienced progression of disease into HSIL. For positivity of p16/Ki-67 dual stained cytology, Sensitivity (45.5%) for the detection of HSIL or specificity (82.1%) for normal or low grade cytology was higher than those of HPV 16/18 tests (18.2% and 89.9%, respectively) (p=0.025). Conclusion p16/Ki-67 dual stained cytology could provide both high sensitivity and specificity for the prediction of HSIL in Pap cytology in the future. Positive p16/Ki-67 dual-stained cytology in low grade cytology was highly associated with the progression of disease in 1 or 2 years follow-up. Therefore, in cases of positive dual-stained cells morphologically showing benign atypical features, further follow-up would be necessary. Disclosure: Nothing to disclose.